Florence Foster Jenkins [compact disc] : original motion picture soundtrack - Streep, Meryl; Waller, Fats, 1904-1943; Garifullina, Aida; Helberg, Simon; Charles, Ernest, 1895-1984; Strauss, Johann, 1825-1899; McHugh, Jimmy, 1894-1969; Delibes, Léo, 1836-1891; Delibes, Léo, 1836-1891; Chopin, Frédéric, 1810-1849; Chopin, Frédéric, 1810-1849; Mozart, Wolfgang Amadeus, 1756-1791; et al. (Decca, 2016)
Along with Alexandre Desplat's score, this soundtrack features performances from the film's cast, including Meryl Streep and Simon Helberg. There are also tracks from Fats Waller, Anne Sofie Von Otter, and Bengt Forsberg.